Ambitious instruction and student achievement: Evidence from early career teachers and the TRU math observation instrument. (September 2022) - Kim, Jihyun; Salloum, Serena; Lin, Qinyun; Hu, Sihua
Abstract: What constitutes effective instructional practices in improving student achievement continues to elude practitioners and researchers. Researchers have offered evidence on the association between different instructional practices and student achievement using various tools, but some aspects of instructional practices, such as formative assessment, were left out. Using TRU Math to capture rich elementary mathematics observation data coupled with student achievement data, we found that the extent to which teachers surface students' ideas and build upon these ideas has significant associations with student achievement in mathematics. We also provide vivid descriptions of high quality instruction compared to lower quality instruction. Highlights: What constitutes effective instructional practices in improving student achievement remains a black box. The extent to which teachers surface student ideas is associated with student achievement. High-quality teaching is related to meaningful collaboration among teachers and active use of formative assessment.